THE KIRKPATRICK MODEL AS A FRAMEWORK FOR EVALUATING TEACHER TRAINING PROGRAMS AT THE NATIONAL CENTER FOR EDUCATIONAL QUALITY ASSURANCE - Nurjannah Nurjannah; Sitti Mania; Muhammad Nur Akbar Rasyid (Jurnal Kajian Pendidikan dan Psikologi, 2026)
The evaluation of teacher education and training programs is a crucial step in ensuring the quality of efforts to enhance educators’ competencies. One of the most widely used evaluation models in the context of training is the Kirkpatrick Model. This conceptual article aims to examine the relevance and applicability of the Kirkpatrick Model as a comprehensive framework for evaluating teacher training programs. The Kirkpatrick Model offers four interconnected levels of evaluation: reaction, learning, behavior, and results. Each level provides a different perspective on assessing program success, ranging from participant satisfaction to tangible impacts in the workplace. In the context of teacher training, this model can be used not only to measure participants’ cognitive and affective achievements but also to assess changes in teaching practices and contributions to improving the quality of education in schools. This article emphasizes that the use of the Kirkpatrick Model requires systematic evaluation planning, the collection of valid and reliable data, and the involvement of various stakeholders. Furthermore, this approach enables training organizers to objectively identify a program’s strengths and weaknesses, thereby providing a foundation for designing continuous improvements. Thus, the Kirkpatrick Model serves not only as a tool for measuring program success but also as a strategic instrument for decision-making and the formulation of more effective and impactful teacher training policies.